Serum osteoprotegerin level is positively associated with peripheral artery disease in patients with peritoneal dialysis. Issue 1 (1st January 2020) - Lin, Wei-Chen; Tsai, Jen-Pi; Lai, Yu-Hsien; Lin, Yu-Li; Kuo, Chiu-Huang; Wang, Chih-Hsien; Hsu, Bang-Gee
Abstract: Osteoprotegerin (OPG) is a potential biomarker of cardiovascular disease complications and severity. Peripheral arterial disease (PAD) is associated with an increased risk of death in patients on peritoneal dialysis (PD). Therefore, this study aimed to evaluate the relationship between serum OPG levels and PAD by measuring the ankle-brachial index (ABI) of patients on PD. A commercial enzyme-linked immunosorbent assay kit was used to measure OPG values. Left or right ABI values of <0.9 were categorized as the low ABI group. Among 70 patients on PD, 13 (18.6%) were categorized in the low ABI group. Patients in the low ABI group had higher prevalence of diabetes mellitus ( p = .044) and higher serum C-reactive protein (CRP) ( p < .001) and OPG levels ( p < .001) but lower creatinine ( p = .013) and peritoneal Kt/V ( p = .048) levels than those in the normal ABI group. Results of multivariable logistic regression analysis revealed that OPG [adjusted odds ratio (aOR) 1.027, 95% confidence interval (CI) 1.010–1.045, p = .002] and CRP (aOR 1.102, 95% CI 1.006–1.207, p = .037) levels were independent predictors of PAD in patients on PD. OPG can also be used to predict PAD development with the area under the receiver operating characteristic curve of 0.823 (95% CI: 0.714–0.904, p < .001) in patients on PD. Therefore, serum OPG and CRP levels can be considered as risk factors for PAD development in patients on PD.